Peran Public Relation Dalam Menarik Minat Peserta Didik Baru Di Madrasah Aliyah Al-Manaar Muhammadiyah Pameungpeuk Kabupaten Garut. - Ilham Al-Muqsith; Sa'diyah El Adawiyah (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Intense competition between educational institutions is currently increasingly felt. Schools, both public and private, use various methods to attract the attention of the public. One way is to maximize the role of public relations in promoting the school to attract the interest of prospective new students and be able to improve the school's image. The aim of this research is to provide a complex description regarding the role of public relations in attracting the interest of prospective new students at Madrasah Aliyah Al-Manaar Muhammadiyah Pameungpeuk, Garut Regency, Academic Year 2023/2024. This research uses a descriptive qualitative approach. Data collection methods use observation, interviews and documentation. The research results show that the role of public relations in attracting the interest of new students at Madrasah Aliyah Al-Manaar Muhammadiyah Pameungpeuk Garut Regency for the 2023/2024 academic year includes: creating institutional programs b) helping to publicize institutional programs c) being a mediator between school institutions and the community .